The trend of vegetation greening and its drivers in the Agro-pastoral ecotone of northern China, 2000–2020. (October 2021) - Pei, Hongwei; Liu, Mengzhu; Jia, Yugui; Zhang, Hongjuan; Li, Yali; Xiao, Yuxiao
Highlights: 95% of the agro-pastoral ecotone of northern China is greening from 2000 to 2020. Vegetation greening is more significant than previously observed. Human-induced impacts are responsible for 66% of vegetation changes. Vegetation greening is unsustainable as a whole, and may degrade extensively. Abstract: Revegetation practices have continued for nearly 20 years in the agro-pastoral ecotone of northern China (AENC), but it still remains unknown how human-induced efforts have contributed to vegetation restoration. This study analyzed the spatiotemporal dynamics of vegetation coverage in the AENC during 2000–2020 in terms of the normalized difference vegetation index (NDVI) using MODIS NDVI datasets, projected the future trend of vegetation variations, and was first to quantify the relative contributions of climatic and anthropogenic impacts on the vegetation variations in the AENC by residual analysis. The results showed that the vegetation in the AENC was greening in recent 20 years due to pronounced increases in NDVI at a rate of 0.00623 year −1, but the trend of vegetation greening was unsustainable as a whole, especially in the central AENC, where large areas of vegetation will degrade in the future. Specifically, anthropogenic and climatic impacts jointly determined vegetation greening in almost 89% of the AENC. Human activities, especially large-scale afforestation, was the most important driver that contributed to vegetation greening in the AENC as a result of the relative role of approximately 66% of NDVI variations (34% from climate change). Despite the significant expansion in forest coverage, excessive afforestation had complex and unpredictable impacts on vegetation growth, and hence the eco-restoraiton is better to make vegetation recover in its natural form. This study revealed a more significant NDVI uptrend in the AENC than previously understood, highlighted the decisive role of human activities in vegetation greening over the last 20 years, and was expected to offer a better understanding and information for local ecological restoration.